Study of vitamins in pulmonary Tuberculosis - Dalvi, Shubhangi M.; Patil, Vinayak W.; Ramraje, Nagsen N.; Yeram, Neelam; Meshram, Priti (International Journal of Research in Medical Sciences, 2019)
Background: In recent years, progress in Tuberculosis (TB) control and eradication has been threatened by the emergence of drug resistant strains of Mycobacterium tuberculosis (MTB). Several studies describe micronutrient malnutrition in TB. This study focuses on the effect of drug resistance and disease progression on levels of various vitamins. Methods: The case control study comprised of 50 normal healthy human volunteers (Control), 50 newly diagnosed TB patients (CAT I) and 50 TB patients showing multi drug resistance (MDR). Recruited subjects were of both genders in age group of 18- 60 years and from different socioeconomic status. Blood serum samples analysed for levels of Vitamin A, Vitamin D, Vitamin E, Vitamin C, Vitamin B12 and Folic acid by using Spectrophotometer, ELISA and Chemiluminescence instruments. Statistical evaluation was done for correlation among variables. Results: The levels of vitamins in TB patients were significantly reduced when compared with controls. Also, MDR-TB patients showed severe malnourished state in comparison to those who were newly diagnosed for the disease. Conclusions: There is a need to provide vitamin supplements in proper sufficient dosage with anti-TB drugs during treatment, which will help fight against the disease and ensure rapid recovery of the patients.